Research Progress and Hotspot Analysis on Acupuncture and Moxibustion Treatment of Mild Cognitive Impairment - Zhang, Chi; Su, Tongsheng; Wan, Zhaoxin; Sun, Jiarui (Journal of Contemporary Medical Practice, 2024)
Objective: Based on CiteSpace software, the literature on the treatment of mild cognitive impairment (MCI) by acupuncture in the past 20 years was analyzed, and the progress track and hot trends of acupuncture in the treatment of MCI were summarized. Methods: Chinese journal articles from January 1, 2004 to November 1, 2024 were retrieved from CNKI database and converted into CiteSpace software using Endnote X9 and Citespace6.3. R1 software analyzes keywords and draws knowledge map. The research progress and hotspot of acupuncture in the treatment of mild cognitive impairment were analyzed. Results: A total of 611 literatures were included, and it was found that the number of literatures on the treatment of MCI by acupuncture continued to increase in recent years, including acupuncture, electroacupuncture, clinical trials, etc. Conclusion: Visualization software was used to analyze the research hotspot of acupuncture in the treatment of mild cognitive impairment. Head electroacupuncture, RCT test, neuroprotection and repair of acupuncture, cognitive improvement, comprehensive treatment mode, prevention of dementia may be the research hotspot and trend in this field. In the past 20 years, the research on acupuncture in the treatment of mild cognitive impairment in Chinese literature has mainly focused on the observation of clinical efficacy and the exploration of mechanism of action. In addition, the clinical treatment methods of acupuncture and moxibustion are also continuously optimized, and the research on its mechanism of action is also continuously deepened. These trends reveal the potential and importance of acupuncture in the treatment of mild cognitive impairment.